Hemorphins as activity regulators of interactions between the nervous and the immune systems and the hypothalamo-pituitary-adrenocortical axis - N. H. Barkhudaryan; H. H. Zakaryan (ՀՀ ԳԱԱ հրատ.)
Hemorphins, a family of endogenous nonclassical opioid peptides derived from hemoglobin (Hb), exert a wide spectrum of biological activity by affecting different receptors function. Հեմորֆինները հեմոգլոբինից (Hb) առաջացած ոչ դասական էնդոգեն օպիոիդ պեպտիդների ընտանիք են, որոնք օժտված են կենսաբանական ակտիվության լայն սպեկտրով, ազդելով տարբեր ռեցեպտորների ֆունկցիայի վրա: Геморфины являются семейством эндогенных неклассических опиоидных пептидов, предшественником которых является гемоглобин (Hb). Они обладают широким спектром биологической активности, воздействуя на функции различных рецепторов.
Keywords: Biology; Biochemistry